PENGARUH PENAMBAHAN FLY ASH TERHADAP KUALITAS SEMEN DI PT SEMEN BATURAJA. Tbk - Maghpiroh, Ana; Iskandar, Damayanti; anaser, Novadri; tohir, Safaruddin (DE FACTO : Journal Of International Multidisciplinary Science, 2023)
Fly Ash or fly ash is solid waste produced from burning coal in power plants. Fly Ash was previously obtained from the simple production of burning coal with a gas funnel and dispersed into the atmosphere. The use of Fly Ash in OPC type cement has been carried out with varying percentages of 2%, 4%, 6%, 8%, 10%, 12%, 14%. The test was carried out by adding an additive (Fly Ash) to the basic material for making OPC cement. Next, testing the composition of the properties of Fly Ash using X-ray, testing the physical properties of cement, namely testing compressive strength and setting time, while testing the chemical properties of cement was carried out using the Insoluble Parts and SO3 tests. From the results of this research, it was found that the addition of Fly ash had a positive impact on compressive strength, cement setting time, and SO3. Where the addition of Fly ash from low to high percentages can increase the fineness of the cement so that it affects the setting time and compressive strength of the cement. From this research, it was found that the addition of additives (Fly ash) can improve the quality of OPC cement, and in general it is not much different from the physical properties of PCC cement.